Reconceptualization of the Role of Religious Courts in Resolving Sharia Economic Disputes Following the Legal Reform of the Judicial System - Abd Warits; Jaya Roza Azzukhrufi; Nur Aida Tahirulla; Bahrudin Zamawi (Yayasan Pendidikan Islam Almatani, 2026)
This study aims to analyze the scope and implementation of the authority of the Religious Court in resolving Islamic economic disputes following the enactment of Law No. 3 of 2006. The research focuses on a case study at the Sumenep Religious Court, which has jurisdiction over disputes involving Islamic financial institutions, including Islamic banking, Islamic financing, and Islamic insurance. This study employs a qualitative socio-legal research method that integrates normative legal analysis with empirical data. Data were collected through in-depth interviews with judges and court officials, direct observation of court proceedings, and examination of relevant legal documents and court decisions.The findings indicate that the Religious Court possesses absolute authority to examine, adjudicate, and resolve Islamic economic disputes as stipulated in Article 49 of Law No. 3 of 2006. The implementation of this authority at the Sumenep Religious Court has been concretely realized through several court decisions addressing disputes between Islamic financial institutions and their customers. These decisions demonstrate the court’s increasing role and capacity in handling complex Islamic economic cases in accordance with sharia principles and national law. The originality of this research lies in its empirical focus on the practical application of the Religious Court’s authority at the regional level, providing new insights into how statutory mandates are operationalized in resolving Islamic economic disputes.